Characterization of Gastric and Neuronal Histaminergic Populations Using a Transgenic Mouse Model - Walker, Angela K.; Park, Won-Mee; Chuang, Jen-Chieh; Perello, Mario; Sakata, Ichiro; Osborne-Lawrence, Sherri; Zigman, Jeffrey M. (PLOS ONE, 2013)
Histamine is a potent biogenic amine that mediates numerous physiological processes throughout the body, including digestion, sleep, and immunity. It is synthesized by gastric enterochromaffin-like cells, a specific set of hypothalamic neurons, as well as a subset of white blood cells, including mast cells. Much remains to be learned about these varied histamine-producing cell populations. Here, we report the validation of a transgenic mouse line in which Cre recombinase expression has been targeted to cells expressing histidine decarboxylase (HDC), which catalyzes the rate-limiting step in the synthesis of histamine. This was achieved by crossing the HDC-Cre mouse line with Rosa26-tdTomato reporter mice, thus resulting in the expression of the fluorescent Tomato (Tmt) signal in cells containing Cre recombinase activity. As expected, the Tmt signal co-localized with HDC-immunoreactivity within the gastric mucosa and gastric submucosa and also within the tuberomamillary nucleus of the brain. HDC expression within Tmt-positive gastric cells was further confirmed by quantitative PCR analysis of mRNA isolated from highly purified populations of Tmt-positive cells obtained by fluorescent activated cell sorting (FACS). HDC expression within these FACS-separated cells was found to coincide with other markers of both ECL cells and mast cells. Gastrin expression was co-localized with HDC expression in a subset of histaminergic gastric mucosal cells. We suggest that these transgenic mice will facilitate future studies aimed at investigating the function of histamine-producing cells.